Analysis of Legal Protection for Third Parties as Owners of Collateral Objects of Mortgage Rights : Case Study of Cirebon Religious Court Decision Number 808/Pdt.G/2021/PA CN - Arie Herawati; Ramlani Lina Sinaulan; Joko Sriwidodo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The involvement of a third party in a debt agreement as the owner of the collateral object is a legal act that often occurs in society. Not a few third parties feel disadvantaged due to the debt agreement between the debtor and the creditor because there are still no regulations that clearly regulate their legal protection, one of the cases is Decision Number 808 / Pdt.G / 2021 / PA CN This study aims to examine problems related to legal protection for third parties as owners of collateral according to applicable laws and regulations. This research method uses a normative legal approach by approaching the laws in force in Indonesia, then a normative analysis is carried out using data sources in the form of laws and regulations, court decisions, opinions of legal experts, along with existing legal concepts. This study will later focus on legal protection for third parties as collateral owners based on applicable regulations and legal settlements if third parties feel disadvantaged by the collateral object they own. From the results of the study, it can be concluded that there is no prohibition on the involvement of third parties as guarantors of land rights in the debt agreement process, however, legal regulations regarding the role of third parties are only explained implicitly in Law No. 4/1996, resulting in third parties being vulnerable to being harmed. As a form of legal protection for third parties, it can be done through a preventive process by issuing APHT and SKMHT by authorized officials, in addition, if the third party's rights have been harmed, it can be taken through litigation and non-litigation.